Nomadic Lactobacilli as cell factory for antibiofilm therapy - Paul, Linette Shoby; Hameed, Hamitha Chinganadi; K. V., Leela; Sharma, Ashu; Lee, Jintae; Shemesh, Moshe; Rajasekharan, Satish Kumar (Frontiers in Cellular and Infection Microbiology, 2025)
Vulvovaginal candidiasis (VVC) is an infection caused by Candida albicans that presents an escalating threat to humans. Lactobacilli may play a critical role in maintaining microbiome balance in the gut and vagina as well as limiting fungal colonization, including C. albicans. Certain Lactobacilli, classified as nomadic groups is gaining immense popularity in antifungal defense due to its unique morphological adaptations. One significant adaptation is the V-shaped cell chaining observed under low pH conditions governed by the LuxS-mediated quorum-sensing system. This structural adaptation potentiates altered secondary metabolite secretion. These geometric forms are not solely survival responses but reflect a structurally coordinated strategy that enhances both antibiofilm and antihyphal activities. In this perspective, we argue that morphology-driven transitions identify nomadic Lactobacilli as a promising frontier in probiotic therapy. By shifting from conventional probiotic formulations to structured microbial interventions, we propose the development of novel sustainable therapeutics for anticandidal therapy.